2021
DOI: 10.3390/en14020351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intake and Exhaust Ducts on the Recovery Efficiency of Heat Recovery Ventilation Systems

Abstract: The heat recovery efficiency of ventilation systems utilizing heat recovery ventilators (HRVs) depends not only on the heat recovery efficiency of the HRV units themselves but also on the intake and exhaust ducts that connect the HRV units to the outside environment. However, these ducts are often neglected in heat loss calculations, as their impact on the overall heat recovery efficiency of HRV systems is often not understood and, to the knowledge of the authors, a mathematical model for the overall heat reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…They pointed out that the lower heat recovery efficiency significantly impacted the ventilation energy in the cold climate. Marsik et al [26] investigated the impact of ducts on recovery efficiency and found that the very long and less insulated intake/exhaust ducts caused the overall heat recovery efficiency to be lower than 30%, despite the utilized heat recovery unit with the heat transfer efficiency of 70%. The heat recovery system has been studied deeply from the aspect of the component and system levels or the energy-saving potential for the whole building in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out that the lower heat recovery efficiency significantly impacted the ventilation energy in the cold climate. Marsik et al [26] investigated the impact of ducts on recovery efficiency and found that the very long and less insulated intake/exhaust ducts caused the overall heat recovery efficiency to be lower than 30%, despite the utilized heat recovery unit with the heat transfer efficiency of 70%. The heat recovery system has been studied deeply from the aspect of the component and system levels or the energy-saving potential for the whole building in previous studies.…”
Section: Introductionmentioning
confidence: 99%